6-6x-3=-57+4x-10

Simple and best practice solution for 6-6x-3=-57+4x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-6x-3=-57+4x-10 equation:


Simplifying
6 + -6x + -3 = -57 + 4x + -10

Reorder the terms:
6 + -3 + -6x = -57 + 4x + -10

Combine like terms: 6 + -3 = 3
3 + -6x = -57 + 4x + -10

Reorder the terms:
3 + -6x = -57 + -10 + 4x

Combine like terms: -57 + -10 = -67
3 + -6x = -67 + 4x

Solving
3 + -6x = -67 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + -6x + -4x = -67 + 4x + -4x

Combine like terms: -6x + -4x = -10x
3 + -10x = -67 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + -10x = -67 + 0
3 + -10x = -67

Add '-3' to each side of the equation.
3 + -3 + -10x = -67 + -3

Combine like terms: 3 + -3 = 0
0 + -10x = -67 + -3
-10x = -67 + -3

Combine like terms: -67 + -3 = -70
-10x = -70

Divide each side by '-10'.
x = 7

Simplifying
x = 7

See similar equations:

| 6i/9-6i | | -x+2x^2+3x=0 | | -78=-5b-3 | | x/9=202 | | 18x+7=7y-13 | | (2x-6)-1/3(9-4x) | | 53=1-4p | | 3(3.2)+2y=32 | | -6-2r=-6 | | 4x-7=5-(2-x) | | 58=-5n-2 | | x+6+8=10-9 | | 63k^2+12k-96=0 | | 7j-7j+j+2j-j=10 | | 205=x+y | | P-15=20 | | F(x)=x-x+1 | | 110=-9-7k | | 5x+2(32-5x)=48 | | b^2-11b=10 | | -7x+10+8x=4+x+6 | | 10y+x=4(x+y) | | p^4-10p+9=0 | | X^4-3x^3+0x^2+x-3=0 | | 12×4/5 | | 4+7=3-4 | | 22=11.1 | | 3600=20x+15y | | F(x)=1-x | | 7×2/12= | | 6z+2z=7z-5 | | -79p+6p-2p+6+42= |

Equations solver categories